Exploring body size of modern South American fur seal (Arctocephalus australis) for osteometric studies in zooarchaeological remains from northern Patagonia, Argentina - Borella, Florencia (2015)
In order to assess the role of pinnipeds in prehistoric subsistence of hunteregatherers from northern Patagonia, traditional osteometric studies based on modern collections of Arctocephalus australis (Aa) and Otaria ﬂavescens (Of) with known age and sex are being employed with the aim of identifying species, sex and age-classes found in zooarchaeological assemblages. A preliminary research based on a very small sample of Aa from the Uruguayan coast suggested the absence of changes in the skull size of this species during the last ﬁve decades. Of skull size reduction through time was observed as a consequence of a density-dependence process in northern and central Patagonia. In this study we discuss the use of modern analogues for the study of zooarchaeological remains of Aa. With this objective in mind, osteometrical data from modern skulls of 30 adult male Aa collected along northern and central Pata- gonia were analysed to assess potential diachronic changes in body size of this species. The results showed that there is no evidence of change in the body size during the last three decades (1990e2013) in the Aa population from northern and central Patagonia. This result supports the relevance of in- vestigations if there are differences in the body size of living individuals that will be employed as an- alogues, for evaluating the potential of these measurements before using them in the analysis of zooarchaeological remains. The use of modern animals of Aa in osteometric analysis of fur seal assemblages recovered in archaeological sites at northern Patagonia is reasonable.